Continuity of CVD treatment during the COVID-19 pandemic: evidence from East Java, Indonesia - Aksari Dewi; Elizabeth Pisani; Bachtiar Rifai Pratita Ihsan; Ayuk Lawuningtyas Hariadini; Anushka Patel; Anna Palagyi; Devarsetty Praveen; Sujarwoto; Diana Lyrawati (Taylor & Francis Group, 2023)
Abstract Background In Indonesia, the world's fourth most populous country, cardiovascular diseases (CVDs) are a leading cause of death and disability. Government efforts to reduce the burden of CVD include a community-based prevention and early detection programme, and the provision of medicines to prevent cardiovascular events. Disruptions to medicine supply chains, service provision, and movement during the COVID-19 pandemic potentially threatened the continuity of these efforts. We investigated the distribution and dispensing of common CVD medicines in Malang district, East Java, before the pandemic and early in its course. Methods From January to October 2020, we collected monthly data on stock levels, sales or dispensing volumes, and price for five common CVD medicines (amlodipine, captopril, furosemide, glibenclamide and simvastatin), from a public and a private distributor, and from public health facilities (n = 4) and private pharmacies (n = 2). We further complied monthly data on patient numbers in two primary health centres. We tracked changes in stocks held and volumes dispensed by medicine type and sector, comparing the three months before the local COVID-19 response was mobilised with the subsequent seven months. We conducted interviews with pharmacists (n = 12), community health workers (n = 2) and a supply chain logistics manager to investigate the reasons for observed changes, and to learn details of any impacts or mitigation measures. Results The pandemic affected demand more than supply, causing medicine stocks to rise. Restricted service provision, lock-down measures and fear of infection contributed to a sharp drop in patient numbers and dispensing volumes in the public sector. Meanwhile private sector sales, especially of lower-priced CVD medicines, rose. Community health workers attributed some poor health outcomes to interruption in regular patient check-ups; this interruption was aggravated by formal mitigation policies. Conclusions Fears that COVID-19 would interrupt medicine availability were unfounded in East Java. Public sector patients may have compensated for reduced service access by switching to private pharmacies. Mitigation policies that ignored administrative procedures were not effective.